Morphometric and Enzymatic Changes in Gills of Rainbow Trout After Exposure to Suboptimal Low Temperature - Elias Lahnsteiner; Nooshin Zamannejad; Anna Dünser; Franz Lahnsteiner (Current Issues in Molecular Biology, 2025)
The present study investigated the influence of a 30 day exposure of rainbow trout (Oncorhynchus mykiss) to a suboptimal low temperature of 1.8 ± 1.0 °C on their different gill characteristics (morphometry, enzyme activities, and expression of genes) in comparison to fish acclimated to 9.4 ± 0.1 °C. Morphometric analysis revealed a significant decrease in the distance between the secondary lamellae at the low temperature, which can be interpreted as a decrease in the effective gill surface. The epithelial thickness increased at the lower temperatures, which is considered a mechanism to reduce ion fluxes and save the energy costs for osmoregulation. The length of the primary lamellae, distance between the primary lamellae, length of the secondary lamellae, as well as the number of mucus cells, chloride cells, and capillaries per mm of the secondary lamella were similar between the temperature regimes. The enzymatic activities of pyruvate kinase and malate dehydrogenase were significantly increased in cold-exposed fish, whereas lactate dehydrogenase activity was higher in controls, indicating increased energy expenditure and adjustments in energy metabolism. The activities of carbonic anhydrase, caspase, Na+/K+ ATPase, and H+ ATPase, and the gene expressions of hif1a, ca2, rhCG, slc26a6, and slc9a1 showed no statistically significant differences between the two temperature regimes. Therefore, it can be concluded that ammonia transport, acid–base regulation, and osmoregulation were not affected by the tested low temperature regime. These findings highlight that exposure to suboptimal temperatures induces structural and metabolic modifications in rainbow trout gills, potentially as an adaptive response to thermal stress. This study contributes to the understanding of fish acclimation to cold environments, with implications for aquaculture and ecological resilience in changing climates.